COVID-19 vaccines for low- and middle-income countries - Choi, Edward M (Trans R Soc Trop Med Hyg, 2021)
The COVID-19 pandemic is the biggest threat to public health in a century. Through hard work and ingenuity, scientists have developed a number of safe and effective vaccines against COVID-19 disease. However, demand far outstrips supply and countries around the world are competing for available vaccines. This review describes how low- and middle-income countries access COVID-19 vaccines, what is being done to distribute vaccines fairly, as well as the challenges ahead.